Pengembangan Lembar Kerja Siswa (LKS) Berbasis Mind Mapping untuk Meningkatkan Penguasaan Konsep Belajar pada Materi Interaksi Makhluk Hidup dan Lingkungannya - Bambang Waras Rianto; Tabitha Sri Hartati Wulandari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
In the global era, the use of LKS is needed as teaching materials, because LKS can accelerate the growth of students' learning interest, but the use of LKS has not used the proper method of learning. The result of observation shows that learning still uses conventional method, so that the students' learning interest is less which result in mastery of concept is still below 75%. Efforts to overcome these problems by developing LKS with Mind Mapping method. This development research using R & D method with ADDIE model, with the aim to produce LKS with Mind Mapping method that can improve the mastery of learning concept by looking validas, practicality, and effectiveness. The results of the validation of 84.78% showed the valid category, the practical value of 72.5% with the good category, the effectiveness of LKS obtained from the classical learning achievement of 90% with very high category and student response of 100% with very strong category. The conclusion that the development result of LKS is declared eligible to be used as teaching material.